The readiness of IIUM nursing and medical students towards interprofessional education - Ayu Farah Hana, Mohamed; Ahayalimudin, Nurul'Ain (2014)
Introduction: In health care setting, client reports higher level of satisfaction, better acceptance of care and improved health outcomes following treatment by a collaborative team. However, there might be some barriers for the healthcare professionals to collaborate well. Interprofessional education (IPE) can help to solve this situation by increase confidence, further understanding among profession and allows for better communication among and between professions. There is a crucial need of IPE, especially to the students.